Pendampingan Perumusan Penggunaan Nomenklatur “Putusan” Jenis Produk Hukum MPR RI - Syamsul, E. Mulya (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2023)
The purpose of this service activity is to analyze whether the MPR's authority over the form of "ruling" is still relevant or not. This activity uses the Focus Group Discussion (FGD) method facilitated by the MPR RI Secretariat Assessment Board on November 2, 2023 at the Fieris Kertajati Hotel, Majalengka Regency. The results obtained that the MPR RI has two types of products that are regeling and beschiking as regulated in other regulations. The provisions of the People's Consultative Assembly of the Republic of Indonesia are no longer a hierarchy of Indonesian laws and regulations because they are more of a beschiking decision that does not have basic norms like the basic norms owned by the Law, as for the legal design loophole, if the MPR RI still needs its exsistence, it must reposition the MPR RI as an institution that has the basic norms of Indonesian law under the 1945 Constitution as the main basic norm of nation and state.